2015
DOI: 10.1007/s13524-015-0391-4
|View full text |Cite
|
Sign up to set email alerts
|

Black-White Differences in Attitudes Related to Pregnancy Among Young Women

Abstract: In this paper we use newly available data from the Relationship Dynamics and Social Life (RDSL) study to compare a wide range of attitudes related to pregnancy for 961 Black and white young women. We also investigate the extent to which race differences are mediated by, or net of, family background, childhood socioeconomic status, adolescent experiences related to pregnancy, and current socioeconomic status. Black women are less positive, in general, than white women, toward young non-marital sex, contraceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 74 publications
(74 reference statements)
5
42
0
Order By: Relevance
“…Other research has demonstrated that black women are more negative than white women about contraception, especially oral contraceptive pills (Barber et al 2015; Gilliam et al 2009). They perceive more side effects of hormonal contraception (Guzzo and Hayford 2012; Kaye et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other research has demonstrated that black women are more negative than white women about contraception, especially oral contraceptive pills (Barber et al 2015; Gilliam et al 2009). They perceive more side effects of hormonal contraception (Guzzo and Hayford 2012; Kaye et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these negative attitudes may reflect mistrust of healthcare providers partly because of the historical association between the family planning movement and eugenics, unethical medical testing on vulnerable populations, and forced sterilization, although these mechanisms are difficult to test. In addition, because black women are more negative than white women about sex, and have lower expectation for sex in the near future (Barber et al 2015), they may eschew methods that require a great deal of advance planning, such as oral contraceptives, in favor of methods that can be provided by men or procured at the last minute (e.g., condoms). Black women also face a high risk of STIs (CDC 2014), and condoms are highly effective for STI prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related but distinct concept is attitude toward motherhood. African American women describe motherhood as meaningful and a source of respect [20] and are more likely to perceive pregnancy as having positive consequences [21]; however, attitude toward motherhood has not been examined in relation to contraceptive use. These outlooks could impact decisions around contraceptive use, as could attitudes toward and past experience with contraceptives [22].…”
Section: Introductionmentioning
confidence: 99%
“…Women’s perceptions of relationship trust [21, 26], relationship commitment [27], and the male partner’s desire for a pregnancy [23] may play a role in contraceptive use. These relationship qualities have been independently examined in studies of contraceptive use, but there is a gap in knowledge related to their potential combined influence.…”
Section: Introductionmentioning
confidence: 99%